(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2021)
Monograph "Management of the development of higher education of Ukraine in the European educational space "will be useful both for scientists, students, teachers interested in processes Managing the development of higher education in Ukraine in the context of the functioning of the European Space higher education, and for practitioners involved in the management of higher educational institutions.